THE USE OF SWEAR WORDS IN PEWDIEPIE’S YOUTUBE VIDEOS - Octavia Wulandari (UIN Alauddin Makassar, 2017)
AbstractThis research discussed about, the use of swear words uttered by PewDiePie’s in his Youtube Videos which aimed to show the types of swear word found in the PewDiePie’s videos, and to show the dominant types of swear words based on the meaning and meaningless swearing. This research was descriptive qualitative method. The object of the study were five videos from Pewdiepie’s Youtube channel which collected based on most viewed videos on his Youtube channel. The researcher used note taking as the instruments in order to get the valid data. The findings showed that there were five types of swear words that used in PewDiePie’s videos those were: 14 data of Dysphemistics, 38 data of Idiomatically, 1 data of Abusively, 24 data of Emphatically, 27 data of Carthartically. The researcher conclude that the dominant type of swearing that Pewdiepie used in his videos is SW2 which does not have any intrinsic meaning at all (categorized as Emphatic swearing and Idiomatic swearing) rather it is merely a word that could express the feeling towards other people without offend someone’s pride.AbstrakPenelitian ini membahas tentang, penggunaan kata-kata umpatan yang diucapkan oleh PewDiePie dalam Video Youtube-nya yang bertujuan untuk menunjukkan jenis kata umpatan yang ditemukan dalam video PewDiePie, dan untuk menunjukkan tipe kata umpatan yang dominan berdasarkan makna dan sumpah tanpa arti. Penelitian ini merupakan penelitian deskriptif kualitatif. Objek penelitian ini adalah lima video dari saluran Youtube Pewdiepie yang dikumpulkan berdasarkan video yang paling banyak dilihat di saluran Youtube-nya. Peneliti menggunakan catatan sebagai instrumen untuk mendapatkan data yang valid. Temuan menunjukkan bahwa ada lima jenis kata umpatan yang digunakan dalam video PewDiePie yaitu: 14 data Dysphemistics, 38 data Idiomatically, 1 data Abusively, 24 data secara emosional, 27 data Cartrama. Peneliti menyimpulkan bahwa jenis sumpah yang dominan yang digunakan Pewdiepie dalam videonya adalah SW2 yang sama sekali tidak memiliki makna intrinsik (dikategorikan sebagai sumpah Emphatic dan sumpah Idiomatik), melainkan hanya sebuah kata yang bisa mengungkapkan perasaan terhadap orang lain tanpa menyinggung kebanggaan seseorang.